Case report: Neuronal intranuclear inclusion disease presenting with acute encephalopathy - Bu, Julia Ting; Torres, Dolores; Robinson, Adam; Malone, Corey; Vera, Juan Carlos; Daghighi, Shadi; Dunn-Pirio, Anastasie; Khoromi, Suzan; Nowell, Justin; Léger, Gabriel C.; Ciacci, Joseph D.; Goodwill, Vanessa S.; et al. (Frontiers in Neurology, 2023)
Neuronal intranuclear inclusion disease (NIID), a neurodegenerative disease previously thought to be rare, is increasingly recognized despite heterogeneous clinical presentations. NIID is pathologically characterized by ubiquitin and p-62 positive intranuclear eosinophilic inclusions that affect multiple organ systems, including the brain, skin, and other tissues. Although the diagnosis of NIID is challenging due to phenotypic heterogeneity, a greater understanding of the clinical and imaging presentations can improve accurate and early diagnosis. Here, we present three cases of pathologically proven adult-onset NIID, all presenting with episodes of acute encephalopathy with protracted workups and lengthy time between symptom onset and diagnosis. Case 1 highlights challenges in the diagnosis of NIID when MRI does not reveal classic abnormalities and provides a striking example of hyperperfusion in the setting of acute encephalopathy, as well as unique pathology with neuronal central chromatolysis, which has not been previously described. Case 2 highlights the progression of MRI findings associated with multiple NIID-related encephalopathic episodes over an extended time period, as well as the utility of skin biopsy for antemortem diagnosis.